Degradable polyester and preparation method thereof
By inserting methylene groups into the PET molecular chain, the conjugation stability effect is interrupted, weak polar bonds are activated, and the inherently degradable modified PET polyester is prepared, which solves the problem of difficult degradation of PET and achieves efficient recycling and environmentally friendly degradation effects of PET polyester.
Patent Information
- Application Number
- CN202510024302.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-07
AI Technical Summary
PET is difficult to degrade in nature, and landfill or incineration treatment has huge harm to the environment. The existing degradation methods are costly and have low recycling rates, which limit the development of PET recycling industrialization.
By inserting methylene groups into the PET molecular chain, the conjugation stabilization effect between the benzene ring and the formate group is interrupted, and weak polar bonds are activated to prepare intrinsically degradable modified PET polyester.
The inherent degradability of PET polyester is achieved, while maintaining good thermal stability, and improving the environmental recycling rate of PET waste.
Smart Images

Figure BDA0005232295840000011 
Figure BDA0005232295840000076 
Figure BDA0005232295840000078
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of degradation and modification of polyester materials, and in particular to a degradable polyester and a preparation method thereof. Background Art
[0002] Polyethylene terephthalate (PET) is a versatile thermoplastic polymer material widely used in synthetic fibers in the textile industry or packaging plastics for food and beverage products. The PET linear polymer chain is composed of terephthalic acid and ethylene glycol structural units, which are connected by an unstable polar formate group, making the macromolecule sufficiently reactive to different tertiary recycling options. However, PET is difficult to degrade in nature, and landfill or incineration treatment causes great harm to the environment. A large amount of waste PET urgently needs to be recycled.
[0003] In recent years, as people pay more attention to environmental protection, the concept of sustainable development has become a hot topic. On June 1, 2022, the two recommended national standards "Degradation Performance and Labeling Requirements for Biodegradable Plastics and Products" and "Biodegradable Drinking Straws" were officially implemented, which means that the promotion and application of degradable materials and products will be greatly accelerated. Regarding PET degradation, the most studied methods at home and abroad are chemical methods and enzyme degradation methods. Many scholars believe that both have greater exploration value and more far-reaching development prospects than physical methods; however, the above methods cannot fundamentally solve the problem. High cost, low recycling rate and slow technological development have become important factors currently limiting the industrialization of PET recycling. The present invention uses the basic principle of electronic effect to activate and modify the PET molecular chain structure, insert methylene between the benzene ring and the formate group to interrupt the strong conjugated stabilization effect, and make PET polyester an intrinsically degradable sustainable polymer material, thereby solving the environmental pollution problem of PET waste. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a degradable polyester and a preparation method thereof. The present invention interrupts the conjugated stabilizing effect of the PET polyester molecular chain by inserting a methylene group to activate the polar weak bonds in its chemical structure, so that the prepared modified PET polyester is not only intrinsically degradable but also has good thermal stability.
[0005] In order to achieve the above object, the technical solution of the present invention is:
[0006] A degradable polyester, the chemical structural formula of the degradable polyester is:
[0007]
[0008] In the formula, 0 represents no group, R Ar For Fang support, R CA is cycloalkane, (0 / RAr / R CA ) means that there is no group between two -CH2- or it is an aryl group or a cycloalkyl group, and the degree of polymerization n is a natural number ≥25.
[0009] Furthermore, the arylene is phenylene, biphenylene, naphthylene, furanylene, thiopheneylene or pyrroleylene, and the cycloalkylene is cyclopentylene or cyclohexylene.
[0010] The present invention also provides a method for preparing the above-mentioned degradable polyester, which comprises: firstly, the aromatic diacetic acid or aromatic diacetate monomer and the diol monomer are polymerized in the early stage by melt esterification or ester exchange, and then polycondensed in the later stage. In the early stage of the synthesis reaction, the temperature is raised to 190-200° C. in an inert atmosphere for esterification or ester exchange; in the later stage, the temperature is raised to 200-240° C. in a vacuum for polycondensation to obtain the degradable polyester.
[0011] Furthermore, the preparation method of the degradable polyester comprises the following steps:
[0012] Step 1, preliminary polymerization: weigh aromatic diacetic acid or aromatic diacetate monomer and diol monomer, mix them, add catalyst; under nitrogen atmosphere, heat to 190-200° C., react under mechanical stirring, distillation and condensation, start timing when the first drop of water or alcohol by-product is distilled out, and esterification or ester exchange reaction is carried out for 2.5-3.5 hours until no by-product is distilled out.
[0013] Step 2, late polycondensation: add a polycondensation catalyst; maintain mechanical stirring, turn off the nitrogen atmosphere, remove the distillation condensation, and evacuate to less than 200 Pa; heat to 200-240° C. for polycondensation reaction for 3.0-4.5 hours until no vacuum bubbles are extracted, pour the reactants into an evaporating dish while hot, and vacuum dry to obtain a crude polyester product.
[0014] Step 3, purifying the crude product: dissolving the crude polyester product in a mixed solvent of trifluoroacetic acid and chloroform, using a mixed precipitant of ethylene glycol and methanol to reprecipitate the polyester product from the mixed solvent, filtering, washing (preferably washing three times with a mixed precipitant), and finally vacuum drying to obtain a degradable polyester.
[0015] Preferably, in step 1, the aromatic diacetate monomer is diethyl terephthalate monomer, and the diol monomer is one of ethylene glycol, terephthalic acid methanol or 4,4'-biphenyl dimethanol monomer.
[0016] Preferably, in step 1, the molar ratio of the aromatic diacetic acid or aromatic diacetate monomer to the diol monomer is 1:(1-2.2).
[0017] Furthermore, in step 1, the catalyst is one or more metal acetates; in step 2, the polycondensation catalyst is one metal acetate.
[0018] Preferably, in step 1, the catalyst is one or more of manganese acetate, magnesium acetate and zinc acetate; in step 2, the polycondensation catalyst is antimony acetate.
[0019] Preferably, in step 1, the molar ratio of the catalyst to the aromatic diacetic acid or aromatic diacetate monomer is [(5×10 -4 )~(2×10 -3 )]: 1; in the step 2, the molar ratio of the polycondensation catalyst to the aromatic diacetic acid or aromatic diacetate monomer is [0~(8×10 -4 )]:1.
[0020] More preferably, the chemical structure of the degradable polyester is (O / R Ar / R CA ) is 0: in the step 1, the diol monomer is ethylene glycol monomer, the molar ratio of aromatic diacetic acid or aromatic diacetate monomer to diol monomer is 1:2.2, the catalyst is manganese acetate, and the molar ratio of catalyst to aromatic diacetic acid or aromatic diacetate monomer is (5×10 -4 ): 1; in the step 2, the polycondensation catalyst is antimony acetate, and the molar ratio of the polycondensation catalyst to the aromatic diacetic acid or aromatic diacetate monomer is (8×10 -4 ):1.
[0021] More preferably, the chemical structure of the degradable polyester is (O / R Ar / R CA ) is R Ar / R CA In step 1, the diol monomer is one of p-phenylenedimethanol or 4,4'-biphenylenedimethanol monomers, the molar ratio of aromatic diacetic acid or aromatic diacetate monomer to diol monomer is 1:1, the catalyst is a mixture of manganese acetate, magnesium acetate and zinc acetate in a molar ratio of 1:1:1, and the molar ratio of the total amount of catalyst to the aromatic diacetic acid or aromatic diacetate monomer is (2×10 -3 ): 1; in the step 2, the amount of the polycondensation catalyst is 0.
[0022] Preferably, in step 1 and step 2, the heating rate is 5°C min -1 , the mechanical stirring rate is 100-200rpm.
[0023] Preferably, in step 2 and step 3, the vacuum drying temperature is 80-100° C., and the vacuum drying time is 48 h and 72 h, respectively.
[0024] Preferably, in step 3, the volume ratio of trifluoroacetic acid and chloroform in the mixed solvent and the volume ratio of ethylene glycol and methanol in the mixed precipitant are both 1:4, and the volume ratio of the mixed solvent to the mixed precipitant is 1:20.
[0025] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0026] 1. Compared with the prior art, the present invention is no longer limited to the study of external degradation methods, but uses the principle of weakening the conjugation effect to promote the heterolytic cleavage of covalent bonds, inserts a methylene group between the benzene ring and the formate group, interrupts the strong p-π-large π-π-p conjugation in the PET molecular chain, activates the ester group CO polar weak bond, and realizes the intrinsic degradability of PET polyester through paradigm molecular modification.
[0027] 2. The degradable modified PET polyester prepared by the present invention is a material matrix resin, which can be used to produce plastics, fibers, films, foams, plates and sheets, etc., which is conducive to the recovery and recycling of these materials and products after they are discarded.
[0028] 3. The present invention adopts bulk polymerization, the product is pure, the operation is simple, no complicated separation and purification process is required, the reactor has a large effective reaction volume, is easy to be continuous, has high production efficiency and low production cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 For the synthesis system of Example 1 1 H NMR spectra: (a, d) ethylene glycol monomer; (b, e) diethyl terephthalate monomer; (c, f) modified PET polyester, namely polyethylene terephthalate (PEP).
[0030] Figure 2 For the synthesis system of Example 1 13 C NMR spectra: (a, d) ethylene glycol monomer; (b, e) diethyl terephthalate monomer; (c, f) modified PET polyester PEP.
[0031] Figure 3 For Example 2 synthesis system 1 H NMR spectra: (a, d) diethyl terephthalate monomer; (b, e) diethyl terephthalate monomer; (c, f) modified PET polyester, namely poly(terephthalate) (PTP).
[0032] Figure 4 For Example 2 synthesis system 13 C NMR spectra: (a, d) diethyl terephthalate monomer; (b, e) diethyl terephthalate monomer; (c, f) modified PET polyester PTP.
[0033] Figure 5 For Example 3 synthesis system1 H NMR spectra: (a, d) 4,4'-biphenyl dimethanol monomer; (b, e) diethyl terephthalate monomer; (c, f) modified PET polyester, namely poly (4,4'-biphenyl dimethyl terephthalate) (PBP).
[0034] Figure 6 For Example 3 synthesis system 13 C NMR spectra: (a, d) 4,4'-biphenyl dimethanol monomer; (b, e) diethyl terephthalate monomer; (c, f) modified PET polyester PBP.
[0035] Figure 7 For the comparative synthesis system 1 H NMR spectra: (a, d) ethylene glycol monomer; (b, e) dimethyl terephthalate monomer; (c, f) PET polyester.
[0036] Figure 8 For the comparative synthesis system 13 C NMR spectra: (a, d) ethylene glycol monomer; (b, e) dimethyl terephthalate monomer; (c, f) PET polyester.
[0037] Fig. 9 For test example 1, 20℃min -1 Differential scanning calorimetry temperature spectra of the modified PET polyester PEP synthesized in Example 1 compared with the PET polyester synthesized in the comparative example at the heating and cooling rates: (a) the second heating cycle; (b) the cooling cycle.
[0038] Fig.10 Scanning electron micrographs of the surface morphology of the samples of (a, c) the PET polyester synthesized in the comparative example and (b, d) the modified PET polyester PEP synthesized in Example 1 before and after hydrolysis at 90°C under the strong alkaline conditions of 3.0M NaOH aqueous solution for 5 hours: (a, b) before hydrolysis; (c, d) after hydrolysis.
[0039] Fig.11 Scanning electron micrographs of the surface morphology of the samples of (a, c) the PET polyester synthesized in the comparative example and (b, d) the modified PET polyester PEP synthesized in Example 1 before and after hydrolysis at 120°C in a 3.0M H2SO4 aqueous solution with strong acidity for 12 hours: (a, b) before hydrolysis; (c, d) after hydrolysis.
[0040] Fig.12 The degradation liquid of (a) the modified PET polyester PEP synthesized in Example 1 and (b) the PET polyester synthesized in the comparative example after alkaline hydrolysis in 3.0M NaOH aqueous solution at 90°C for 5h is shown in Figure 1. 1H NMR spectrum, where (a1, a2) and (b1, b2) are the enlarged views of (a) and (b), respectively.
[0041] Fig.13 The degradation liquid of (a) the modified PET polyester PEP synthesized in Example 1 and (b) the PET polyester synthesized in the comparative example after alkaline hydrolysis in 3.0M NaOH aqueous solution at 90°C for 5h is shown in Figure 1. 13 C NMR spectroscopy.
[0042] Fig.14 In Test Example 1, (a) the modified PET polyester PEP synthesized in Example 1 and (b) the PET polyester synthesized in the comparative example were acidically hydrolyzed in a 3.0M H2SO4 aqueous solution at 120°C for 12 hours. 1 H NMR spectrum: (a) white needle-shaped crystalline product precipitated from the degradation solution; (b) degradation solution.
[0043] Fig.15 In Test Example 1, (a) the modified PET polyester PEP synthesized in Example 1 and (b) the PET polyester synthesized in the comparative example were acidically hydrolyzed in a 3.0M H2SO4 aqueous solution at 120°C for 12 hours. 13 C NMR spectrum: (a) white needle-shaped crystalline product precipitated from the degradation solution; (b) degradation solution.
[0044] Fig.16 In test example 1, 10℃min in nitrogen atmosphere -1 Thermogravimetric analysis temperature spectra of the modified PET polyester PEP synthesized in Example 1 compared with the PET polyester synthesized in the comparative example at the heating rate: (a) thermal weight loss curve; (b) thermal weight loss differential curve.
[0045] Fig.17 For test example 2, 20℃min -1 Differential scanning calorimetry temperature spectra of the modified PET polyesters PTP and PBP synthesized in Examples 2 and 3, respectively, compared with the PET polyester synthesized in the comparative example at the heating and cooling rates: (a) the second heating cycle; (b) the cooling cycle.
[0046] Fig.18 Scanning electron micrographs of the surface morphology of the samples of (a, d) the PET polyester synthesized in the comparative example, (b, e) the modified PET polyester PTP synthesized in Example 2, and (c, f) the modified PET polyester PBP synthesized in Example 3 before and after hydrolysis at 90°C under the strong alkaline condition of 3.0M NaOH aqueous solution for 5 hours: (a, b, c) before hydrolysis; (d, e, f) after hydrolysis.
[0047] Fig.19Scanning electron micrographs of the surface morphology of the samples of (a, d) the PET polyester synthesized in the comparative example, (b, e) the modified PET polyester PTP synthesized in Example 2, and (c, f) the modified PET polyester PBP synthesized in Example 3 before and after hydrolysis at 120°C in the strong acidic condition of 3.0M H2SO4 aqueous solution for 24 hours: (a, b, c) before hydrolysis; (d, e, f) after hydrolysis.
[0048] Fig. 20 The degradation liquid of (a) the modified PET polyester PBP synthesized in Example 3, (b) the modified PET polyester PTP synthesized in Example 2, and (c) the PET polyester synthesized in the comparative example was alkaline hydrolyzed in 3.0M NaOH aqueous solution at 90°C for 5h. 1 H NMR spectra, where (a1), (b1) and (c1) are partial enlarged views of (a), (b) and (c), respectively.
[0049] Fig.21 The degradation liquid of (a) the modified PET polyester PBP synthesized in Example 3, (b) the modified PET polyester PTP synthesized in Example 2, and (c) the PET polyester synthesized in the comparative example was alkaline hydrolyzed in 3.0M NaOH aqueous solution at 90°C for 5h. 13 C NMR spectroscopy.
[0050] Fig. 22 The results are as follows: (a) the modified PET polyester PBP synthesized in Example 3, (b) the modified PET polyester PTP synthesized in Example 2, and (c) the PET polyester synthesized in the comparative example were acidically hydrolyzed in 3.0M H2SO4 aqueous solution at 120°C for 24 hours. 1 H NMR spectrum: (a, b) white needle-shaped crystalline product precipitated from the degradation solution; (c) degradation solution.
[0051] Fig.23 The results are as follows: (a) the modified PET polyester PBP synthesized in Example 3, (b) the modified PET polyester PTP synthesized in Example 2, and (c) the PET polyester synthesized in the comparative example were acidically hydrolyzed in 3.0M H2SO4 aqueous solution at 120°C for 24 hours. 13 C NMR spectrum: (a, b) white needle-shaped crystalline product precipitated from the degradation solution; (c) degradation solution.
[0052] Fig.24 In test example 2, 10℃min in nitrogen atmosphere -1 Thermogravimetric analysis temperature spectra of the modified PET polyesters PTP and PBP synthesized in Examples 2 and 3, respectively, compared with the PET polyester synthesized in the comparative example at the heating rate: (a) thermal weight loss curve; (b) thermal weight loss differential curve. DETAILED DESCRIPTION
[0053] In order to better understand the present invention, the following examples are further described to further illustrate the present invention, but the present invention is not limited to the following examples. Those skilled in the art can make various modifications or adjustments to the present invention, and these equivalent forms are also within the scope of the claims listed in the present application.
[0054] The present invention compares the degradation efficiency of the modified PET degradable polyester prepared in the embodiment with that of the PET polyester prepared in the comparative example through a test example; the drugs and raw materials used in the embodiment, comparative example and test example are all commercially available analytically pure grades unless otherwise specified.
[0055] Embodiment 1:
[0056] A method for preparing a modified PET degradable polyester, namely polyethylene terephthalate (PEP), the method comprising the following steps:
[0057] 1. Preliminary polymerization: weigh 4×10 -2 mol diethyl terephthalate monomer and 8.8×10 -2 10 mol ethylene glycol monomer was placed in a 100 mL four-necked flask (nitrogen atmosphere was introduced into the four flasks respectively, and a mechanical stirrer, a thermometer, and a distillation condensation device were installed, the same below), and manganese acetate catalyst was added. The molar ratio of the catalyst to diethyl terephthalate monomer was (5×10 -4 ): 1; under nitrogen atmosphere, at 5℃min -1 The system is heated at a rate (the same below). When the system approaches 60°C, the diethyl terephthalate monomer melts. At this time, mechanical stirring is turned on and the speed is set to 100 rpm to mix the two monomers evenly. When the temperature continues to rise to 190°C, the stirring is increased to 200 rpm. The time when the first drop of ethanol by-product is distilled out is used as the starting point for timing. The ester exchange reaction is maintained at 190°C for 3.0 to 3.5 hours until no by-product is distilled out, thereby completing the early polymerization.
[0058] 2. Late polycondensation: After the early polymerization is completed, antimony acetate catalyst is added. The molar ratio of the catalyst to diethyl terephthalate monomer is (8×10 -4 ): 1; the temperature was raised to 220°C, and the polycondensation reaction was carried out under stirring at 200rpm for 1h. The viscosity of the system increased significantly. At this time, the nitrogen atmosphere was turned off, the distillation and condensation device was removed, and a vacuum pump was used to evacuate the system to a vacuum degree of 200Pa; the temperature was continued to be raised to 240°C, and the vacuum degree was increased to 100-150Pa. The reaction was stirred for another 3.0-3.5h. The viscosity of the system continued to increase until no vacuum bubbles were extracted. Then, the stirring and vacuuming were stopped. The reactants were poured into an evaporating dish while hot, and vacuum dried at 100°C for 48h to obtain a crude modified PET polyester product.
[0059] 3. Refining the crude product: Take trifluoroacetic acid and chloroform (volume ratio of 1:4) and mix them evenly to prepare a polyester solvent; take ethylene glycol and methanol (volume ratio of 1:4) and mix them evenly to prepare a polyester precipitant; put the dried polyester crude product in a 100mL beaker, add 40mL of polyester solvent thereto, and stir magnetically until the crude product is completely dissolved to form a transparent polyester solution; add 800mL of polyester precipitant in a 1000mL beaker, slowly pour the above polyester solution into the polyester precipitant while stirring with a glass rod, and refrigerate and stand overnight in a refrigerator (4-10℃, 8h, the same below) to allow the polyester to precipitate again and settle to the bottom of the cup; filter the precipitated polyester, wash the filter cake repeatedly three times with a polyester precipitant, and finally vacuum dry at 100℃ for 72h to obtain modified PET polyester PEP.
[0060] Embodiment 2:
[0061] A method for preparing a modified PET degradable polyester, namely poly(terephthalate) (PTP), comprising the following steps:
[0062] 1. Preliminary polymerization: weigh 4×10 -2 mol diethyl terephthalate monomer and 4×10 -2 mol of terephthalic acid methanol monomer was placed in a 100 mL four-necked flask, and manganese acetate, magnesium acetate and zinc acetate catalysts (the molar number of each catalyst is the same). The molar ratio of the total amount of the three catalysts to diethyl terephthalate monomer was (2×10 -3 ): 1; under a nitrogen atmosphere, the system is heated. When the system approaches 60° C., the diethyl terephthalate monomer melts. At this time, mechanical stirring is turned on and the speed is set to 100 rpm to mix the two monomers evenly. When the temperature continues to rise to 190° C., the stirring is increased to 200 rpm. The time when the first drop of ethanol by-product is distilled out is used as the starting point for timing. The ester exchange reaction is maintained at 190° C. for 2.5 to 3.0 hours. The viscosity of the system gradually increases until no by-product is distilled out, and the early polymerization is completed.
[0063] 2. Late polycondensation: After the early polymerization is completed, no catalyst is added; the nitrogen atmosphere is turned off, the distillation and condensation device is removed, and a vacuum pump is used to evacuate the system to a vacuum degree of 200 Pa; the temperature is raised to 220°C, and the polycondensation reaction is carried out under stirring at 200 rpm for 1 hour, and the viscosity of the system is further increased; the temperature is continued to be raised to 240°C, and the vacuum degree is increased to 100-150 Pa, and the reaction is stirred for another 2.0-2.5 hours, and the viscosity of the system continues to increase until no vacuum bubbles are extracted, then stirring and evacuating are stopped, and the reactants are poured into an evaporating dish while hot, and vacuum dried at 100°C for 48 hours to obtain a crude modified PET polyester product.
[0064] 3. Refining the crude product: Take trifluoroacetic acid and chloroform (volume ratio of 1:4) and mix them evenly to prepare a polyester solvent; take ethylene glycol and methanol (volume ratio of 1:4) and mix them evenly to prepare a polyester precipitant; put the dried polyester crude product in a 100mL beaker, add 40mL of polyester solvent thereto, and stir magnetically until the crude product is completely dissolved to form a transparent polyester solution; add 800mL of polyester precipitant in a 1000mL beaker, slowly pour the above polyester solution into the polyester precipitant while stirring with a glass rod, refrigerate and let stand overnight to allow the polyester to precipitate again and settle to the bottom of the cup; filter the precipitated polyester, wash the filter cake repeatedly three times with a polyester precipitant, and finally vacuum dry at 100°C for 72h to obtain modified PET polyester PTP.
[0065] Embodiment 3:
[0066] A method for preparing a modified PET biodegradable polyester, namely poly(4,4'-biphenyl dimethyl terephthalate) (PBP), the method comprising the following steps:
[0067] 1. Preliminary polymerization: weigh 4×10 -2 mol diethyl terephthalate monomer and 4×10 -2 mol 4,4'-biphenyl dimethanol monomer was placed in a 100 mL four-necked flask, and manganese acetate, magnesium acetate and zinc acetate catalysts (each catalyst had the same molar number). The molar ratio of the total amount of the three catalysts to diethyl terephthalate monomer was (2×10 -3 ): 1; under a nitrogen atmosphere, the system is heated. When the system approaches 60° C., the diethyl terephthalate monomer melts. At this time, mechanical stirring is turned on and the speed is set to 100 rpm to mix the two monomers evenly. When the temperature continues to rise to 190° C., the stirring is increased to 200 rpm. The time when the first drop of ethanol by-product is distilled out is used as the starting point for timing. The ester exchange reaction is maintained at 190° C. for 2.5 to 3.0 hours. The viscosity of the system gradually increases until no by-product is distilled out, and the early polymerization is completed.
[0068] 2. Late polycondensation: After the early polymerization is completed, no catalyst is added; the nitrogen atmosphere is turned off, the distillation and condensation device is removed, and a vacuum pump is used to evacuate the system to a vacuum degree of 200 Pa; the temperature is raised to 220°C, and the polycondensation reaction is carried out under stirring at 200 rpm for 1 hour, and the viscosity of the system is further increased; the temperature is continued to be raised to 240°C, and the vacuum degree is increased to 100-150 Pa, and the reaction is stirred for another 2.0-2.5 hours, and the viscosity of the system continues to increase until no vacuum bubbles are extracted, then stirring and evacuating are stopped, and the reactants are poured into an evaporating dish while hot, and vacuum dried at 100°C for 48 hours to obtain a crude modified PET polyester product.
[0069] 3. Refining the crude product: Take trifluoroacetic acid and chloroform (volume ratio of 1:4) and mix them evenly to prepare a polyester solvent; take ethylene glycol and methanol (volume ratio of 1:4) and mix them evenly to prepare a polyester precipitant; put the dried polyester crude product in a 100mL beaker, add 40mL of polyester solvent thereto, and stir magnetically until the crude product is completely dissolved to form a transparent polyester solution; add 800mL of polyester precipitant in a 1000mL beaker, slowly pour the above polyester solution into the polyester precipitant while stirring with a glass rod, refrigerate and let stand overnight to allow the polyester to precipitate again and settle to the bottom of the cup; filter the precipitated polyester, wash the filter cake repeatedly three times with a polyester precipitant, and finally vacuum dry at 100°C for 72h to obtain modified PET polyester PBP.
[0070] Comparative Example:
[0071] A method for preparing PET polyester, the preparation method comprising the following steps:
[0072] 1. Preliminary polymerization: weigh 4×10 -2 mol dimethyl terephthalate monomer and 8.8×10 -2 mol ethylene glycol monomer was placed in a 100 mL four-necked flask, and manganese acetate catalyst was added. The molar ratio of the catalyst to dimethyl terephthalate monomer was (5×10 -4 ): 1; under a nitrogen atmosphere, the system is heated. When the system approaches 140° C., the dimethyl terephthalate monomer melts. At this time, mechanical stirring is turned on and the speed is set to 100 rpm to mix the two monomers evenly. When the temperature continues to rise to 190° C., the stirring is increased to 200 rpm. The time when the first drop of methanol by-product is distilled out is used as the starting point for timing. The ester exchange reaction is maintained at 190° C. for 4.0 to 4.5 hours until no by-product is distilled out, thereby completing the early polymerization.
[0073] 2. Late polycondensation: After the early polymerization is completed, antimony acetate catalyst is added. The molar ratio of the catalyst to dimethyl terephthalate monomer is (8×10 -4 ): 1; the temperature was raised to 240°C, and the polycondensation reaction was maintained at 200rpm for 1h. The viscosity of the system increased significantly. At this time, the nitrogen atmosphere was turned off, the distillation condensation device was removed, and a vacuum pump was used to evacuate the system to a vacuum degree of 200Pa; then the temperature was raised to 250°C, and the reaction was stirred for 1h. The viscosity of the system increased further; the temperature was continued to be raised to 270°C, the vacuum degree was increased to 100-150Pa, and the reaction was stirred for another 2.0-2.5h. The viscosity of the system continued to increase until no vacuum bubbles were extracted. Then the stirring and vacuuming were stopped. The reactants were poured into an evaporating dish while hot, and vacuum dried at 100°C for 48h to obtain a crude PET polyester product.
[0074] 3. Refining the crude product: Take trifluoroacetic acid and chloroform (volume ratio of 1:4) and mix them evenly to prepare a polyester solvent; take ethylene glycol and methanol (volume ratio of 1:4) and mix them evenly to prepare a polyester precipitant; put the dried polyester crude product in a 100mL beaker, add 40mL of polyester solvent thereto, and stir magnetically until the crude product is completely dissolved to form a transparent polyester solution; add 800mL of polyester precipitant in a 1000mL beaker, slowly pour the above polyester solution into the polyester precipitant while stirring with a glass rod, refrigerate and let stand overnight to allow the polyester to precipitate again and settle to the bottom of the cup; filter the precipitated polyester, wash the filter cake repeatedly three times with a polyester precipitant, and finally vacuum dry at 100°C for 72h to obtain PET polyester.
[0075] Testing and Characterization:
[0076] The structures of the modified PET polyesters PEP, PTP and PBP prepared in Examples 1 to 3 and the PET polyester prepared in the comparative example are characterized respectively, and the characterization comprises the following steps:
[0077] 1. Utilize 1 H and 13 C nuclear magnetic resonance spectroscopy was used to characterize the chemical structures of the monomers and their polymerization products, namely, the following were compared and characterized: ethylene glycol monomer, diethyl terephthalate monomer, and PEP in Example 1; terephthalic acid dimethanol monomer, diethyl terephthalate monomer, and PTP in Example 2; 4,4'-biphenyl dimethanol monomer, diethyl terephthalate monomer, and PBP in Example 3; and ethylene glycol monomer, dimethyl terephthalate monomer, and PET polyester in the comparative example.
[0078] Weigh 5-10 mg (for 1 H spectrum test) or 40-50 mg (for 13 C spectrum test) The sample was placed in a nuclear magnetic resonance tube, and 0.5-0.6 mL of deuterated solvent was added to prepare a solution sample. The Bruker Ascend 400 nuclear magnetic resonance spectrometer was used to collect the chemical shift (δ) values of the solution sample. 1 H and 13 C NMR peak. Before preparing the solution sample, the deuterated solvent was fully dried with molecular sieves. The deuterated solvent used for ethylene glycol monomer, diethyl terephthalate monomer, PEP, PTP and dimethyl terephthalate monomer was deuterated chloroform (CDCl3), the deuterated solvent used for terephthalic acid methanol monomer and 4,4'-biphenyl dimethanol monomer was deuterated dimethyl sulfoxide (C2D6SO), the deuterated solvent used for PET polyester was deuterated trifluoroacetic acid (CF3COOD), and the deuterated solvent used for PBP was CF3COOD (for 1 H spectrum test), CDCl3 (for 13 C spectrum test).
[0079] 2. According to the national standard GB / T23942-2009, the metal element content of the residual catalyst in the polyester and its crude product was determined by inductively coupled plasma emission spectrometry: in Example 1 and the comparative example, the manganese and antimony contents in the polyester crude product of step 2 and the polyester of step 3 were compared and determined; in Examples 2 and 3, the manganese, magnesium and zinc contents in the polyester crude product of step 2 and the polyester of step 3 were compared and determined.
[0080] Weigh 100 mg of sample and place it in a polytetrafluoroethylene digestion tube, add 5 mL of 68 wt% concentrated nitric acid, 1 mL of 36-38 wt% concentrated hydrochloric acid and 1 mL of 40 wt% hydrofluoric acid in sequence, digest at 200 ° C for 5 h, transfer to a 25 mL volumetric flask, dilute with deionized water, and let stand for 12 h to prepare a digestion solution sample. Use an Agilent ICP-OES 730 inductively coupled plasma emission spectrometer to first determine the calibration curve, then test the digestion solution, and finally determine the concentration of each metal element in the sample based on the calibration curve.
[0081] 3. According to the national standard GB / T1632.1-2008, the degree of polymerization of polyester (viscosity-average degree of polymerization, the same below) was tested using the intrinsic viscosity method: the degree of polymerization of modified PET polyester PEP, PTP, PBP was compared with that of PET polyester.
[0082] Weigh 0.2500g, For polyester samples, 50 mL of a mixed solvent of phenol and 1,1,2,2-tetrachloroethane (the mass ratio of phenol to tetrachloroethane was 1:1, the same below) was used to prepare the concentrations of c, (c=0.5g dL -1 ) sample solution. After filtering the solution with a filter head, use an Ubbelohde viscometer (inner diameter 0.5-0.6 mm) in a 25°C constant temperature water bath to measure its average outflow time (the median of five test values, the same below); similarly, the average elution time of the mixed solvent (i.e. 0c) was determined
[0083] The one-point method was used to estimate the three concentrations (C, C = c, The intrinsic viscosity of the sample [η] (dL g -1 ):
[0084]
[0085] The molecular weights of the three concentrations of samples were estimated using the following Mark-Houwink empirical equation: (g mol -1 ) (viscosity average molecular weight, the same below):
[0086]
[0087] Here, it is assumed that, like PET polyester, the relationship between intrinsic viscosity and molecular weight of polyesters PEP, PTP and PBP in a mixed solvent of phenol and 1,1,2,2-tetrachloroethane at 25°C approximately conforms to the above Mark-Houwink equation, that is, the two constants of the four polyesters are both 2.1×10 -4 Finally, among the three polymerization degree values obtained by dividing the molecular weight by the molar mass of the repeating unit, the median value is taken as the polymerization degree test value of the sample.
[0088] Test Example 1:
[0089] A comparative test of the degradation efficiency of a modified PET degradable polyester PEP (Example 1) and a PET polyester (Comparative Example), the comparative test comprising the following items in sequence:
[0090] Project 1: According to the national standard GB / T19466-2004, the crystallization properties of polyester were determined by differential scanning calorimetry: the thermal transition behaviors of PEP and PET polyester were compared.
[0091] Using a Netzsch DSC 214 differential scanning calorimeter, the temperature and heat flow were calibrated with indium standard metal and the concentration was 20 mL min -1 The test was conducted under nitrogen atmosphere. Weigh 5-10 mg of sample, seal it in an aluminum crucible, and place it in the sample chamber; another blank aluminum crucible was sealed and placed in the reference chamber. -1 The rate was increased from room temperature (25°C, the same below) to 300°C to eliminate the effect of sample preparation history; then at 20°C min -1 From 300℃ to -60℃; finally at 20℃min -1 From -60℃ to 300℃. In the cooling and second heating cycles, the heat flow (W g -1 ) temperature spectrum with temperature (℃). In the temperature spectrum of cooling (or second heating), the peak point (℃) and peak area (J g -1 ) are defined as the temperature and enthalpy of crystallization (or melting), respectively; in the second temperature increase spectrum, the inflection point (°C) of the step is defined as the glass transition temperature (or transition temperature).
[0092] Project 2: Conduct polyester degradation experiments: Compare the acidic and alkaline hydrolysis experiments of PEP and PET polyester under the same conditions.
[0093] The alkaline hydrolysis experiment includes the following steps:
[0094] Step 1: Preparation of alkaline water degradation agent: weigh 30g NaOH and place it in a 500mL beaker, slowly add 200mL deionized water, and stir with a glass rod until it is completely dissolved; after the solution is cooled to room temperature, transfer it to a 250mL volumetric flask, make up to volume with deionized water, and let it stand overnight to prepare a 3.0M NaOH aqueous solution.
[0095] Step 2: Implementation of the degradation experiment: Using Wuhan Ruiming SZS-20 micro injection molding machine, the sample powder is added into the barrel for sufficient preheating and tamping, and injected into the mold cavity under compressed air pressure at 230°C (for PEP) or 270°C (for PET polyester) to form injection-molded sample strips (the same below); the injection-molded sample strips are cut into 10mm×5mm×2mm rectangular specimens; four specimens are selected, weighed (total) and placed in a 250mL two-necked flask (the two flasks are respectively equipped with a mechanical stirrer and a reflux condenser, the same below), 50mL of the alkaline water prepared in step 1 is added, and reflux reaction is carried out at 90°C and 500rpm for 5h under mechanical stirring.
[0096] Step 3: Degradation sample collection: take out the residual sample and wash it repeatedly three times with deionized water; filter the degradation liquid, and recover the filtered residual debris and filtrate respectively; wherein, the debris is repeatedly washed three times with deionized water, combined with the washed residual sample, vacuum dried at 80°C for 48h, and weighed (total); take 10mL of the filtrate and seal it in a sample bottle as the degradation liquid sample to be tested.
[0097] The acid hydrolysis experiment includes the following steps:
[0098] Step 1: Preparation of acid water degradation agent: In a 500mL beaker, add 200mL of deionized water, then slowly pour in 41.5mL of concentrated H2SO4 (mass fraction 98.3%), and stir with a glass rod to mix; after the solution is cooled to room temperature, transfer it to a 250mL volumetric flask, make up to volume with deionized water, and let it stand overnight to prepare a 3.0M H2SO4 aqueous solution.
[0099] Step 2: Implementation of degradation experiment: Cut the injection molded sample strips into 10mm×5mm×2mm rectangular specimens; select four specimens, weigh them (total) and place them in a 250mL two-necked flask, add 50mL of the acid water prepared in step 1, and reflux for 12h at 120°C and 500rpm mechanical stirring.
[0100] Step 3: Degradation sample collection: Take out the residual sample, wash it repeatedly three times with deionized water, vacuum dry it at 80°C for 48 hours, and weigh it; for PEP, filter the degradation liquid, recover the white needle-shaped crystalline product precipitated therein, wash and dry it like the sample, and then test it; for PET polyester, no product is precipitated in the degradation liquid, directly take 10mL of the degradation liquid and seal it in a sample bottle for testing.
[0101] Project 3: According to the JY / T0584-2020 standard, the surface morphology of polyester in the degradation experiment was observed with the help of scanning electron microscopy technology: the surfaces of PEP and PET polyesters before and after acidic and alkaline hydrolysis experiments were compared and observed.
[0102] The surface morphology of the samples was observed using a Hitachi SU 8010 scanning electron microscope. The samples to be tested were adhered to the stage using conductive glue, and after platinum spraying, they were transferred into the microscope sample chamber for observation.
[0103] The samples before acidic and alkaline hydrolysis are the rectangular samples before the reaction in the acidic and alkaline hydrolysis step 2 in the degradation experiment of Project 2, respectively. The samples after acidic and alkaline hydrolysis are the residual samples after drying in the acidic and alkaline hydrolysis step 3 in the degradation experiment of Project 2, respectively.
[0104] Project 4: Use the weighing method to determine the mass loss rate of polyester in the degradation experiment: Compare and estimate the weight loss rate of PEP and PET polyester after hydrolysis compared with that before hydrolysis in acidic and alkaline hydrolysis experiments.
[0105] The mass loss rate (%) of the polyester sample was estimated by the following equation:
[0106]
[0107] In the formula, m AD (g) is the sample mass before degradation experiment, m PD (g) is the mass of the sample after degradation experiment.
[0108] During acidic and alkaline hydrolysis, m AD It is the total weight of the four samples before the reaction in the acidic and alkaline hydrolysis step 2 of the degradation experiment in Project 2; in the case of alkaline hydrolysis, m PD The total weight of the residual pieces and debris after drying in step 3 of alkaline hydrolysis in the degradation experiment of project 2. For acid hydrolysis, m PD Weigh the residual sample after drying in the acid hydrolysis step 3 of the degradation experiment in Project 2.
[0109] Project 5: Utilization 1 H and 13 C nuclear magnetic resonance spectroscopy was used to analyze the chemical structure of polyester after degradation experiments: the products of PEP and PET polyester in the degradation liquid after acidic and alkaline hydrolysis experiments were compared and analyzed respectively.
[0110] A Bruker Ascend 400 NMR spectrometer was used to collect the chemical shift (δ) values of the solution samples. 1 H and 13C NMR peak. Before preparing solution samples, the deuterated solvent was fully dried using molecular sieves.
[0111] After alkaline hydrolysis, 0.1 mL of the degradation solution to be tested packaged in step 3 was taken and placed in a nuclear magnetic resonance tube, and 0.6 mL of deuterated water (D2O) was added to prepare a solution sample.
[0112] After acid hydrolysis: For PEP, take 5 mg (for 1 H spectrum test) or 20-30 mg (for 13 C spectrum test) Step 3: Filter and recover the white needle-shaped crystalline product to be tested in the degradation solution after drying, place it in a nuclear magnetic tube, and add 0.6mL CF3COOD to prepare a solution sample; for PET polyester, the sample is prepared in a similar manner to that after alkaline hydrolysis.
[0113] Project 6: According to GB / T33047-2016 and JY / T0589.5-2020 standards, use thermogravimetric analysis to characterize the thermal stability of polyester: compare the thermal decomposition temperatures of PEP and PET polyesters.
[0114] A TA Instruments SDT Q600 thermogravimetric-differential thermal analyzer was used to analyze the -1 The test was conducted in a nitrogen atmosphere. Two empty Al2O3 crucibles were placed on the two trays of the balance in the furnace and leveled; 3-5 mg of the dried polyester sample was weighed and placed in the outer crucible, and the furnace was turned off; the temperature was set at 10 °C min -1 The rate is increased from room temperature to 800°C, and the weight of the sample and the rate of change of weight with temperature are recorded in real time. The temperature corresponding to the weight loss of 5% is defined as the thermal decomposition temperature.
[0115] Test Example 2:
[0116] A comparative test of the degradation efficiency of a modified PET degradable polyester PTP and PBP (Examples 2 and 3) and a PET polyester (Comparative Example), the comparative test includes the following items in sequence:
[0117] Project 1: According to the national standard GB / T19466-2004, the crystallization properties of polyester were determined by differential scanning calorimetry: the thermal transition behaviors of PTP, PBP and PET polyester were compared.
[0118] The specific test method is the same as item 1 in test example 1. In addition, the crystallization enthalpy ΔH mc (J g -1 ), the crystallinity of the sample X c (%) is estimated by the following equation:
[0119]
[0120] In the formula, is the ideal melting enthalpy when the crystallinity reaches 100% theoretically, and assuming that the PTP and PBP Both with PET polyester Literature value (117.6 J g -1 )quite.
[0121] Project 2: Conduct polyester degradation experiments: Compare the acidic and alkaline hydrolysis experiments of PTP, PBP and PET polyester under the same conditions.
[0122] When preparing the injection-molded sample strips in the acidic and alkaline hydrolysis experiments, the injection molding temperature of PTP and PBP was 230°C, and the injection molding temperature of PET polyester was 270°C.
[0123] In the alkaline hydrolysis experiment, residual flakes and debris were produced in the degradation solutions of PTP, PBP and PET polyester; in the acidic hydrolysis experiment, white needle-shaped crystalline products were precipitated in the degradation solutions of PTP and PBP, but no products were precipitated in the degradation solution of PET polyester.
[0124] The specific alkaline hydrolysis experimental method is the same as item 2 in test example 1.
[0125] The specific acid hydrolysis experimental method is similar to item 2 in test example 1; the difference is that the reflux reaction time in the corresponding step 2 is 24 hours.
[0126] Project 3: According to the JY / T0584-2020 standard, the surface morphology of polyester in the degradation experiment was observed with the help of scanning electron microscopy technology: the surfaces of PTP, PBP and PET polyesters before and after acidic and alkaline hydrolysis experiments were compared and observed.
[0127] The specific observation method is the same as item 3 in test example 1.
[0128] Project 4: Use the weighing method to determine the mass loss rate of polyester in the degradation experiment: compare and estimate the weight loss rate of PTP, PBP and PET polyester after hydrolysis compared with that before hydrolysis in acidic and alkaline hydrolysis experiments.
[0129] The specific estimation method is the same as item 4 in test example 1.
[0130] Project 5: Utilization 1 H and 13 C nuclear magnetic resonance spectroscopy was used to analyze the chemical structure of polyester after degradation experiments: the products of PTP, PBP and PET polyester in the degradation liquid after acidic and alkaline hydrolysis experiments were compared and analyzed respectively.
[0131] The specific analysis method after alkaline hydrolysis is the same as item 5 in Test Example 1.
[0132] The specific analytical method after acid hydrolysis is similar to that of item 5 in test example 1, where the sample preparation of PTP and PBP is similar to that of PEP; the difference is that the deuterated solvent used for the sample preparation of PTP and PBP is CDCl3; for PBP, since less white needle-shaped crystals are precipitated in its degradation solution, 2 mg is taken for 1 H spectrum test and 5mg for 13 C spectrum test.
[0133] Project 6: According to GB / T33047-2016 and JY / T0589.5·2020 standards, the thermal stability of polyester was characterized by thermogravimetric analysis: the thermal decomposition temperatures of PTP, PBP and PET polyester were compared.
[0134] The specific test method is the same as item 6 in test example 1.
[0135] Test Results
[0136] 1. Nuclear magnetic resonance spectroscopy results:
[0137] Depend on Figure 1 and Figure 2 It can be seen that the chain chemical structure of the polymer products (c, f) in Example 1 is clear relative to the monomers (a, d; b, e): 1 H NMR spectroscopy ( Figure 1 The three resonance peaks in c) are respectively attributed to the modified PET polyester PEP repeating unit ( Figure 1 f) Three chemical environments of H atoms; 13 C NMR spectroscopy ( Figure 2 The five resonance peaks in c) are respectively attributed to the PEP repeating unit ( Figure 2 f) five chemical environments of C atoms; two figures ( Figure 1 c, 2c) and no other impurity peaks were obviously seen; these indicated that the polymerization product was a modified PET polyester PEP with relatively high purity and was successfully synthesized.
[0138] Similarly, by Figure 3 and Figure 4 It can be seen that the modified PET polyester PTP in Example 2 was successfully synthesized; Figure 5 and Figure 6 It can be seen that the modified PET polyester PBP in Example 3 was successfully synthesized; Figure 7 and Figure 8 It can be seen that the PET polyester in the comparative example was successfully synthesized.
[0139] 2. Inductively coupled plasma optical emission spectroscopy results:
[0140] It can be seen from Table 1 that in Examples 1 to 3 and the comparative example, compared with the polyester crude product obtained in step 2, the metal element content of the residual catalyst in the PEP, PTP, PBP and PET polyester obtained in step 3 decreased by nearly two orders of magnitude (from 10 -4 to 10 -6 gg -1 ), indicating that after refining, the residual catalysts in the four polyesters were effectively removed, which eliminated the influence of the catalysts on the subsequent degradation reactions to the greatest extent and increased the comparability of the subsequent comparative degradation experiments.
[0141] Table 1 The metal element content of the residual catalyst in the crude products of the modified PET polyesters PEP, PTP and PBP prepared in Examples 1 to 3 respectively and the PET polyester prepared in the comparative example compared with the four
[0142]
[0143] 3. Intrinsic viscosity method results:
[0144] It can be seen from Table 2 that the degrees of polymerization of the polyesters PEP, PTP and PBP prepared in Examples 1 to 3 and the PET polyester prepared in the comparative example are 29, 32, 30 and 31 (taking the median of the three degrees of polymerization values), respectively, that is, the degrees of polymerization of the four polyesters are equivalent, which eliminates the effect of the degree of polymerization on the subsequent degradation reaction to the greatest extent and increases the comparability of the subsequent comparative degradation experiments.
[0145] Table 2 Intrinsic viscosity ([η]), molecular weight of modified PET polyesters PEP, PTP and PBP prepared in Examples 1 to 3 and PET polyesters prepared in the comparative example and degree of polymerization
[0146]
[0147]
[0148] Note: In the table, c = 0.5 g dL -1 , “·” indicates not applicable.
[0149] Test case 1 results:
[0150] 1. Before conducting comparative degradation experiments on PEP and PET polyesters, the important factor affecting the degradation efficiency, crystallization performance, was investigated. Fig. 9 It can be seen that compared with PET polyester, which undergoes glass transition at 78.0°C ( Fig. 9 a) and obvious crystallization at 204.8℃ ( Fig. 9 b), the glass transition temperature of PEP dropped significantly to 6.8℃ ( Fig. 9 a) and does not crystallize ( Fig. 9b), revealing that the large planar rigid structure formed by strong conjugation was interrupted by the insertion of methylene, making the PEP molecular chain significantly flexible, so that it does not crystallize thermodynamically. As expected, amorphous PEP is more easily penetrated by degradation agents than crystalline PET polyester, resulting in increased degradation efficiency.
[0151] 2. By Fig.10 It was observed that before alkaline hydrolysis, PET polyester ( Fig.10 a) and PEP( Fig.10 b) The surface is smooth and crack-free. However, after alkaline hydrolysis etching, the surface morphology of the two polyesters is significantly different: PET polyester ( Fig.10 c) Surface holes and cracks are small and few; but PEP ( Fig.10 d) A large number of holes and cracks are obviously generated on the surface, and the surface layer is completely degraded and peeled off, leaving grooves of varying depths.
[0152] Similarly, by Fig.11 It was observed that before acid hydrolysis, PET polyester ( Fig.11 a) and PEP( Fig.11 b) The surface is smooth and crack-free. However, after acid hydrolysis etching, PET polyester ( Fig.11 c) Only a few superficial wrinkles appeared on the surface, but PEP ( Fig.11 d) A large number of holes, grooves and even debris are obviously produced on the surface.
[0153] Therefore, during acidic and alkaline hydrolysis, the surface etching degree of PEP is significantly higher than that of PET polyester, that is, the degradation efficiency of modified PET polyester PEP is much higher than that of PET polyester.
[0154] 3. As shown in Table 3, the mass loss rates of PET polyester and PEP were 5.9% and 89.3% respectively during alkaline hydrolysis, while the mass loss rates of the two were 0.3% and 90.6% respectively during acidic hydrolysis. These comparative data show that under acidic and alkaline conditions, polyester PEP is significantly more lost to the degradation liquid through hydrolysis than PET polyester, that is, the degradation efficiency of PEP is much higher than that of PET polyester.
[0155] Table 3 In the acidic and alkaline hydrolysis experiments, the mass (m) before the degradation experiment of the modified PET polyester PEP prepared in Example 1 compared with the PET polyester prepared in the comparative example AD ), mass after degradation experiment (m PD ) and mass loss rate
[0156]
[0157] 4. In terms of chemical structure, Fig.12It can be seen that after alkaline hydrolysis, the PEP degradation solution showed 6.95, 3.35 and 3.24 ppm 1 H resonance peak ( Fig.12 a: a1, a2), respectively attributed to the H on the 2,3 position of the benzene ring of terephthaloyloxy, the ethylene H of ethylenedioxy, and the methylene H of terephthaloyloxy; while the PET polyester degradation liquid only weakly appeared 7.60ppm 1 H resonance peak ( Fig.12 b: b1, b2), attributed to the H at the 2,3-position C of the benzene ring of terephthaloyloxy. Fig.13 In the PEP degradation solution after alkaline hydrolysis, 181.11, 135.12, 129.14 and 43.91 ppm appeared 13 C resonance peak ( Fig.13 a), respectively attributed to the carbonyl C of terephthaloyloxy, C at 1,4 position and C at 2,3 position of benzene ring, and methylene C; while the PET polyester degradation liquid only produced 128.62ppm with a very low signal-to-noise ratio 13 C resonance peak ( Fig.13 b), the carbon atoms at positions 2 and 3 of the benzene ring are attributed to terephthaloyloxy. Fig.12 ,13 The spectral data revealed that the PEP degradation liquid was rich in the alkaline hydrolysis products of disodium terephthalate and disodium ethylene glycol, while the PET polyester degradation liquid contained very little alkaline hydrolysis products of disodium terephthalate and disodium ethylene glycol.
[0158] Fig.14 The white needle-shaped crystals precipitated from the PEP degradation solution after acid hydrolysis occurred at 8.99 and 5.49 ppm. 1 H resonance peak ( Fig.14 a), respectively attributed to the 2,3 C H and methylene H of the benzene ring of terephthaloyloxy; while no H appeared in the degradation liquid of PET polyester 1 H resonance peak ( Fig.14 b) By Fig.15 It can be seen that the white needle-shaped crystalline products precipitated from the PEP degradation solution after acid hydrolysis appeared at 181.46, 133.41, 131.23 and 41.06 ppm 13 C resonance peak ( Fig.15 a), respectively attributed to the carbonyl C of terephthaloyloxy, C at 1,4 and 2,3 positions of benzene ring, and methylene C; while PET polyester degradation liquid did not 13 C resonance peak ( Fig.15 b). Fig.14 ,15 The spectral data revealed that the PEP degradation liquid was rich in terephthalic acid acid hydrolysis products, and its crystals were precipitated, while the acid hydrolysis products in the PET polyester degradation liquid were so little that they could be ignored.
[0159] Therefore, during acidic and alkaline hydrolysis, the concentration of hydrolysis products in the degradation solution of polyester PEP is much higher than that of PET polyester, that is, the degradation efficiency of PEP is much higher than that of PET polyester.
[0160] In summary, the above comparative degradation experimental test results 2 to 4 (surface morphology, mass loss rate, chemical structure) self-consistently show that compared with the non-degradable PET polyester, the degradation efficiency of the polyester PEP prepared by modification is greatly improved, and it is a degradable polyester.
[0161] The modification of PEP by inserting a methylene group between the benzene ring and the formate group of PET has two main effects by interrupting the strong macroconjugation in the PET molecule: significantly softening the molecular chain so that it no longer crystallizes; greatly reducing the stability of the conjugation and activating the C·O polar weak bond of the ester group. Of the two effects, the former accelerates the penetration of the degradation agent externally, and the latter promotes the heterolytic cleavage of the C·O bond internally; the combination of the two realizes the degradability of PEP. Since the degradation efficiency of polyester PEP is much higher than that of PET polyester, although the external factor (amorphous state) plays a significant role, the realization of degradability is essentially attributed to the internal factor (weak bond activation).
[0162] 5. By Fig.16 It can be seen that the thermal decomposition temperature of PEP is 386.2℃, which is not much lower than the thermal decomposition temperature of PET polyester (415.5℃), and still remains above 350℃. Fig.16 As can be seen from Figure 2, PEP and PET polyester thermally decompose fastest at 455.5°C and 460.9°C, respectively, which are comparable. Therefore, compared with non-degradable PET polyester, polyester PEP maintains higher thermal stability while achieving degradability.
[0163] Test case 2 results:
[0164] In order to further confirm that the main essential reason for the methylene insertion modification to achieve degradability is the activation of weak bonds rather than the amorphous state, Examples 2 and 3, based on Example 1, respectively insert benzene rings and biphenyls with increasing rigidity between the two methylene groups of the ethylene glycol monomer, and use 4,4'-biphenyl dimethanol monomers and 4,4'-biphenyl dimethanol monomers to condense with diethyl terephthalate monomers, respectively, to prepare polyesters PTP and PBP with increased chain rigidity and thus restored crystallinity, and then compare the degradation efficiency with the PET polyester prepared in the comparative example.
[0165] 1. Before conducting comparative degradation experiments on PTP, PBP and PET polyester, examine the crystallization properties. Fig.17 The differential scanning calorimetry temperature spectrum of the three was used to obtain the crystallization performance data in Table 4. Fig. 9As shown in Table 4, the glass transition temperature increases in the order of PEP, PTP, PBP, and PET polyester (6.8→27.7→58.7→78.0℃), indicating that the chain rigidity of PTP and PBP increases compared with that of PEP (although still lower than that of PET polyester), and both have indeed restored significant crystallinity. The crystal phases of PTP, PBP, and PET polyester with increasing chain rigidity gradually "harden", so the crystallization and melting temperatures increase monotonically (T mc :107.8→183.5→204.8℃; T m :175.1→220.1→254.8℃).
[0166] Table 4 Crystallization properties of modified PET polyesters PTP and PBP prepared in Examples 2 and 3 respectively compared with PET polyester prepared in the comparative example
[0167]
[0168] Note: In the table, T g is the glass transition temperature, T mc is the crystallization temperature, ΔH mc is the crystallization enthalpy, T m is the melting temperature, ΔH m is the melting enthalpy, X c For crystallinity.
[0169] According to the order of PBP, PTP, and PET polyesters, the repeating units contain three, two, and one rigid bulky benzene ring, respectively, which causes the free volume between the chain segments to decrease and the interaction force to increase. Therefore, it can be seen from Table 4 that the crystallization enthalpy and melting enthalpy increase monotonically (ΔH mc :43.9→48.1→53.2 J g -1 ; ΔH m :50.9→55.9→57.8 J g -1 ), resulting in the The estimated crystallinity also increases in sequence (37.3→40.9→45.2%). Importantly, the three crystallinity values are not much different; in fact, the crystallinity values of PBP, PTP, and PET polyesters are The value also increases gradually, reaching 117.6 J g for PET polyester. -1 Therefore, the actual crystallinity of the three may be closer, all close to 45.2% of PET polyester.
[0170] The crystallinity of PTP, PBP and PET polyester is similar, which further increases the comparability for characterizing the intrinsic degradation activity (the effect of weak bond activation on degradation efficiency) through comparative degradation experiments.
[0171] 2. By Fig.18 It was observed that before alkaline hydrolysis, PET polyester ( Fig.18 a) With PTP( Fig.18 b) PBP( Fig.18 c) The surface is smooth and crack-free. After alkaline hydrolysis etching, the surface morphology of the three polyesters is significantly different: PET polyester ( Fig.18 d) Surface holes and cracks are small and few; PTP ( Fig.18 e) Huge, deep holes are formed on the surface, the surface layer is severely degraded and peeled off, and PBP ( Fig.18 f) The surface etching degree is moderate, resulting in larger and more holes and cracks.
[0172] Similarly, by Fig.19 It was observed that before acid hydrolysis, PET polyester ( Fig.19 a) With PTP( Fig.19 b) PBP( Fig.19 c) The surface is smooth and crack-free. After acid hydrolysis etching: PET polyester ( Fig.19 d) Only a few superficial fine lines appear on the surface; PTP ( Fig.19 e) The surface is rich in holes, cracks and grooves, while PBP ( Fig.19 f) The surface etching degree is moderate, with some obvious holes and cracks.
[0173] Therefore, during acidic and alkaline hydrolysis, the degradation efficiency of modified PET polyesters PTP and PBP is significantly higher than that of PET polyester; among the first two, the degradation efficiency of PTP is significantly higher than that of PBP.
[0174] 3. As can be seen from Table 5, the mass loss rates of PET polyester, PTP and PBP during alkaline hydrolysis are 7.0%, 93.0% and 16.7% respectively, while the mass loss rates of the three during acidic hydrolysis are 1.0%, 37.6% and 7.0% respectively. These comparative data show that although the degree of acidic hydrolysis is lower than that of alkaline hydrolysis, under acidic and alkaline conditions, PTP and PBP are more hydrolyzed and lost to the degradation liquid than PET polyester, that is, the degradation efficiency of polyester PTP and PBP is significantly higher than that of PET polyester; among the former two, the degradation efficiency of PTP is significantly higher than that of PBP.
[0175] Table 5 In the acidic and alkaline hydrolysis experiments, the degradation weight (m) of the modified PET polyesters PTP and PBP prepared in Examples 2 and 3 respectively compared with the PET polyester prepared in the comparative example AD ), mass after degradation experiment (m PD ) and mass loss rate
[0176]
[0177] 4. By Fig. 20 It can be seen that after alkaline hydrolysis, the PBP degradation solution was 7.93ppm1 H resonance peak ( Fig. 20 a: a1), attributed to the 3,3′ C H of the benzene ring of 4,4'-biphenyldimethoxy; PTP degradation solution produces strong 7.11 and 6.95 ppm 1 H resonance peak ( Fig. 20 b: b1), which are respectively attributed to the 2 and 3 C H of the benzene ring of terephthalyloxy and terephthalyloxy; while the PET polyester degradation liquid only weakly appears 7.13ppm 1 H resonance peak ( Fig. 20 c: c1), attributed to the H at the 2,3-position of the benzene ring of terephthaloyloxy. Fig.21 In the alkaline degradation solution of the three polyesters, 17.10, 16.98, 17.14 ppm, and 57.36, 57.11, or 57.32 ppm occurred. 13 C resonance peaks are attributed to the methyl C and methylene C of the residual ethanol in the molecular sieve, which are the signal peaks of non-hydrolysis products; after alkaline hydrolysis, the PBP degradation solution appears 128.62ppm 13 C resonance peak ( Fig.21 a), C at position 2,2′ of the benzene ring is attributed to 4,4′-biphenyldimethoxy; Fig.21 In b, the PTP degradation solution produced 181.09, 135.11, 129.14 and 43.91 ppm 13 The C resonance peaks are attributed to the carbonyl C of terephthaloyloxy, the C at positions 1,4 and 2,3 of the benzene ring, and the methylene C, which also occur at 140.57, 127.56, and 63.61 ppm. 13 C resonance peaks are attributed to the 1,4-position C and 2,3-position C of the benzene ring of terephthalylene, and methylene C; PET polyester degradation liquid does not produce 13 C resonance peak ( Fig.21 c). Fig. 20 ,21 Spectral data showed that the PTP degradation liquid was rich in alkaline hydrolysis products of disodium terephthalate and disodium terephthalate methanol, the PBP degradation liquid contained alkaline hydrolysis products of disodium terephthalate and disodium 4,4'-biphenyl dimethanol, while the PET polyester degradation liquid contained very little alkaline hydrolysis products of disodium terephthalate and disodium ethylene glycol.
[0178] Fig. 22 In a and b, the white needle-shaped crystalline products precipitated from the acidic degradation solutions of PBP and PTP were 1.26 ppm. 1 The H resonance peak is attributed to the residual water peak of the sample that was not completely dried, which is the signal peak of the non-hydrolysis product; after acid hydrolysis, the white needle-shaped crystalline product precipitated in the PBP degradation solution appeared at 5.16, 4.64 and 3.66 ppm 1 H resonance peak ( Fig. 22a), which were attributed to the hydroxyl H and methylene H of 4,4′-biphenyl dimethanol and the methylene H of terephthalic acid respectively; the white needle-shaped crystalline product precipitated in the PTP degradation solution had strong 7.28, 7.23, 5.10 and 3.66 ppm 1 H resonance peak ( Fig. 22 b), which are respectively attributed to the H on the 2,3 position of the benzene ring of terephthalic acid and terephthalic acid, and the methylene H of terephthalic acid and terephthalic acid; while the degradation liquid of PET polyester did not appear 1 H resonance peak ( Fig. 22 c) By Fig.23 It can be seen that after acid hydrolysis, the white needle-shaped crystal product precipitated from the PBP degradation solution did not appear 13 C resonance peak ( Fig.23 a) This may be because most of the degradation products are dissolved in acid water and very little precipitates, resulting in the product in the solution sample. 13 C concentration is low and the signal is weak; Fig.23 In b, the white needle-shaped crystal product precipitated from the PTP degradation solution had strong peaks of 171.23, 132.96, 129.48 and 40.96 ppm. 13 The C resonance peaks are attributed to the carbonyl C of terephthalic acid, the 1,4 C and 2,3 C of the benzene ring, and the methylene C. Strong peaks of 135.95, 128.32, and 66.29 ppm also occur. 13 C resonance peaks are attributed to the 1,4 C and 2,3 C of the benzene ring of terephthalol, and the methylene C; while the PET polyester degradation liquid does not produce 13 C resonance peak ( Fig.23 c). Fig. 22 ,23 Spectral data show that the PTP degradation liquid is rich in terephthalic acid and terephthalic alcohol acidic hydrolysis products, and crystals are precipitated; the PBP degradation liquid contains terephthalic acid and 4,4'-biphenyl dimethanol acidic hydrolysis products, and crystals are precipitated; while the acidic hydrolysis products in the PET polyester degradation liquid are so few that they can be ignored.
[0179] Therefore, during acidic and alkaline hydrolysis, the concentration of hydrolysis products in the degradation solution of PTP and PBP is significantly higher than that of PET polyester, that is, the degradation efficiency of polyester PTP and PBP is significantly higher than that of PET polyester; similarly, the degradation efficiency of PTP is significantly higher than that of PBP.
[0180] In summary, the above comparative degradation experimental test results 2 to 4 (surface morphology, mass loss rate, chemical structure) self-consistently reveal that compared with the non-degradable PET polyester, the degradation efficiency of the polyesters PTP and PBP prepared by modification are significantly increased, and they are two degradable polyesters; among them, the degradation efficiency of the degradable PTP is significantly higher than that of the degradable PBP, which may be due to the fact that the steric hindrance of the benzene ring in the former in the diol structural unit is smaller than that of the biphenyl in the latter.
[0181] Under fully comparable conditions where the catalysts were effectively removed, the degree of polymerization was equivalent, and the crystallinity was similar, the chain chemical structure of the non-degradable PET polyester was modified to obtain degradable polyesters PTP and PBP, indicating that the insertion of methylene interrupts the strong conjugated stability, thereby activating the ester group's CO polar weak bond, which is the main essential reason for achieving the intrinsic degradability of polyester.
[0182] 5. By Fig.24 It can be seen that the thermal decomposition temperatures of PTP and PBP are 378.1℃ and 373.5℃ respectively, which are not much lower than the thermal decomposition temperature of PET polyester (415.5℃), and both are still maintained above 350℃. Fig.24 In Figure b, PTP and PBP thermally decomposed fastest at 409.6°C and 425.5°C, respectively, which was lower than the fastest thermal decomposition temperature of PET polyester (460.9°C). In general, compared with non-degradable PET polyester, polyester PTP and PBP maintained higher thermal stability while achieving degradability.
[0183] Comprehensive results:
[0184] In the results of Test Example 1, the degradation efficiency of amorphous modified PET polyester PEP is much higher than that of crystalline PET polyester due to the dual effects of weak bond activation caused by strong conjugation interruption due to methylene insertion and amorphization promoting the penetration of degradation agents. In the results of Test Example 2, the degradation efficiency of crystalline modified PET polyesters PTP and PBP is significantly higher than that of crystalline PET polyester due to the main effect of weak bond activation caused by strong conjugation interruption due to methylene insertion. Combining the results of the two test examples, compared with non-degradable PET polyester, modified PET polyesters PEP, PTP and PBP are all degradable polyesters, and the degradation efficiency of the three decreases in turn, but they all maintain a high thermal stability that is not significantly lower than that of PET polyester.
[0185] In summary, the present invention prepares three degradable polyesters with decreasing degradation efficiency and high thermal stability, namely polyethylene terephthalate (PEP), poly(terephthalate dimethyl terephthalate) (PTP) and poly(4,4'-biphenyl dimethyl terephthalate) (PBP), by inserting methylene into the terephthalic acid structural unit and inserting benzene rings and biphenyls into the ethylene glycol structural unit to modify the PET molecular chain, thereby realizing the degradable modification of PET polyester.
[0186] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention; simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A degradable polyester, characterized in that: The chemical structural formula of the degradable polyester is: In the formula, 0 represents no group, R Ar For Fang support, R CA is cycloalkane, (0 / R Ar / R CA ) means that there is no group between two -CH2- or it is an aryl group or a cycloalkyl group, and the degree of polymerization n is a natural number ≥25.
2. The degradable polyester according to claim 1, characterized in that The arylene is phenylene, biphenylene, naphthylene, furanylene, thiopheneylene or pyrroleylene, and the cycloalkylene is cyclopentylene or cyclohexylene.
3. A method for preparing the degradable polyester according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: firstly, aromatic diacetic acid or aromatic diacetate monomer and diol monomer are polymerized in the early stage by melt esterification or ester exchange, and then polycondensed in the later stage.
4. The preparation method according to claim 3, characterized in that: The steps include: Step 1, preliminary polymerization: weigh aromatic diacetic acid or aromatic diacetate monomer and diol monomer, mix them, add catalyst; under nitrogen atmosphere, heat to 190-200° C., react under mechanical stirring, distillation and condensation, start timing when the first drop of water or alcohol byproduct is distilled out, and the esterification or transesterification reaction lasts 2.5-3.5 hours; Step 2, late polycondensation: add a polycondensation catalyst; keep mechanical stirring, turn off the nitrogen atmosphere, remove the distillation condensation, and evacuate to less than 200Pa; raise the temperature to 200-240°C for polycondensation reaction for 3.0-4.5h, pour the reactants into an evaporating dish while hot, and vacuum dry to obtain a polyester crude product; Step 3, purifying the crude product: dissolving the crude polyester product in a mixed solvent of trifluoroacetic acid and chloroform, using a mixed precipitant of ethylene glycol and methanol to reprecipitate the polyester product from the mixed solvent, filtering, washing, and finally vacuum drying to obtain a degradable polyester.
5. The preparation method according to claim 4, characterized in that: In the step 1, the molar ratio of the aromatic diacetic acid or aromatic diacetate monomer to the diol monomer is 1:(1-2.2).
6. The preparation method according to claim 4, characterized in that: In step 1, the catalyst is one or more metal acetates, and the molar ratio of the catalyst to the aromatic diacetic acid or aromatic diacetate monomer is [(5×10 -4 )~(2×10 -3 )]: 1; in step 2, the polycondensation catalyst is a metal acetate, and the molar ratio of the polycondensation catalyst to the aromatic diacetic acid or aromatic diacetate monomer is [0~(8×10 -4 )]:
1.
7. The preparation method according to claim 4, characterized in that: In step 1 and step 2, the heating rate is 5°C min -1 , the mechanical stirring rate is 100-200rpm.
8. The preparation method according to claim 4, characterized in that: In step 2 and step 3, the vacuum drying temperature is 80-100° C., and the vacuum drying time is 48 h and 72 h, respectively.
9. The preparation method according to claim 4, characterized in that: In the step 3, the volume ratio of trifluoroacetic acid and chloroform in the mixed solvent and the volume ratio of ethylene glycol and methanol in the mixed precipitant are both 1:4, and the volume ratio of the mixed solvent to the mixed precipitant is 1:20.
Citation Information
Patent Citations
Bio-degradable polyester and method for preparing same
CN101885838A
Aliphatic-aromatic copolyester and preparation method thereof
CN102838735A
Copolymer of aliphatic polycarbonate and aromatic polyester and preparation method thereof
CN103265689A
Degradable thermoplastic polyester elastomer having side chain, and preparation method thereof
CN107312165A
Improvements in or relating to aromatic polyesters
GB879124A